Data Mining, C4.5 Algorithm, Dec INDEX KEPUASAN PELANGGAN EDUKITS BATAM CENTRE DENGAN MENGGUNAKAN ALGORITMA C45 - Ellvan Reisyer, Kevin Ellvan Reisyer; Harman, Rika (Universitas Putera Batam, 2024)
The term customer satisfaction refers to a situation when customers realize their needs and desires are met or are not met as expected.. Customers are generally satisfied with their experiences. Customer satisfaction determines whether they continue to use the service, while customer dissatisfaction leads to them stopping using it. The result will be the loss of customers for business actors. Developing strategies to improve the satisfaction of customers is one of the most important tasks for business actors. Essentially, C4.5 is a decision tree algorithm that functions in the form of a structured data collection program coded in such a way that it can be used to collect data that has changed and to turn it into a decision tree that consists of a decision rule so that the results of the data can be used to help make a decision. Based on the findings of the research, it appears the factors that are influencing Edukits Batam Center customer satisfaction the most are price, the accessibility of the location, and the quality of the products.